Mobility of Heavy Metals (Pb, Cd, Zn) in the Pampeano and Puelche Aquifers, Argentina: Partition and Retardation Coefficients - Jakomin, Marisa (2015)
The prediction about metals behaviour in soil requires knowledge on their solid-liquid partitioning. Usually it is expressed with an empirical distribution coefficient or Kd, which gives the ratio of the metal concentration in the solid phase to that in the solution. Kd values have been determined for Zn, Pb and Cd from samples representing the two most exploited aquifers in Argentina, Pampeano and Puelche, at three different locations in the province of Buenos Aires. The Pampeano aquifer presented higher Kd values than the Puelche aquifer. Comparing Kd values, different relationships could be observed: (a) Pampeano aquifer: Pb > Zn > Cd, and (b) Puelche aquifer: Pb > Cd > Zn. Kd for Cd seems to be linked to cationic exchange capacity, but solid phases precipitation can be more determining for Pb and Zn.